2011
DOI: 10.1111/j.1708-8208.2009.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Stability of a Hybrid Self-Tapping Implant Compared to a Cylindrical Non-Self-Tapping Implant with Respect to Drilling Protocols in an Ex Vivo Model

Abstract: Hybrid self-tapping implants could achieve a high primary stability which predicts them for use in low-density bone. However, there is still a debate to clarify the influence of under-dimensioned drilling on primary stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 31 publications
2
48
0
2
Order By: Relevance
“…In 2012, Park et al [27] obtained the maximum insertion torque, angular momentum, and total insertion energy by torque curves, although quantitative analyses on whether torque curves were correlated with implant designs were not conducted. Furthermore, most conventional studies on torque have focused on measurement [28–31] of the maximum torque value and/or RT at the time of IT or the relationship between the RFA value and IT and/or RT [6, 13, 16, 18, 32]. The present study was not limited to measurements of IT and RT, as the characteristics of the torque curves were divided into four areas designated as the initial, parallel, tapered, and platform areas, and quantitative analyses were performed for each area.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Park et al [27] obtained the maximum insertion torque, angular momentum, and total insertion energy by torque curves, although quantitative analyses on whether torque curves were correlated with implant designs were not conducted. Furthermore, most conventional studies on torque have focused on measurement [28–31] of the maximum torque value and/or RT at the time of IT or the relationship between the RFA value and IT and/or RT [6, 13, 16, 18, 32]. The present study was not limited to measurements of IT and RT, as the characteristics of the torque curves were divided into four areas designated as the initial, parallel, tapered, and platform areas, and quantitative analyses were performed for each area.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate for osseointegration of dental implants was shown to be very high for many different designs and brands of implants [3][4][5]. Primary stability, which is one of the most important criteria of implant integration and success rate in the early healing phase, depends mainly on the enosseous design of the implant (length, diameter, shape, and thread) besides the surgical technique, volume, and mechanical quality of local bone [3,4]. During the osseointegration period, bone gradually remodels to the implant threads and thus the secondary stability is attained by direct bone to implant contact [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, more than 1,300 types of dental implants are available, in different materials, shapes, sizes, lengths, with different surface characteristics or coatings [2]. The success rate for osseointegration of dental implants was shown to be very high for many different designs and brands of implants [3][4][5]. Primary stability, which is one of the most important criteria of implant integration and success rate in the early healing phase, depends mainly on the enosseous design of the implant (length, diameter, shape, and thread) besides the surgical technique, volume, and mechanical quality of local bone [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…12 In this context, recent studies have shown that in order to induce controlled compression forces in the cortical bone layer during implant insertion, a new hybrid auto-implant has been specifically designed for use in critical-quality bone, which combines the advantages of a conical implant with those of a cylindrical shape. 13 Considering the increase in the complexity of the cases in oral rehabilitations, modifications in the macro-geometry in implants should seek to favor their insertion, promoting the cut and bone compaction to increase their primary stability. 14 This is of extreme importance for regions where there is low bone height and quality, where implant interlocking can be compromised.…”
mentioning
confidence: 99%
“…15 The development of implants with self-drilling apices plays the role of bone shear and compression and may influence the primary stability of the implant, favoring the success of the treatment. 13 To increase the primary stability and osseointegration of dental implants, new implant designs have been developed. Jo and Hobo 16 have shown that implants with their apical portion expanded through a screw can present success rates comparable to conventional implants.…”
mentioning
confidence: 99%